Adaptation strategies to manage summer forage shortages improve animal performance and better maintain milk and cheese quality in grass- versus corn-based dairy systems - M. Bouchon; B. Martin; C. Bord; A. Ferlay; J.M.G. Bloor; M. Eugène; A. Delacroix-Buchet; C. Cebo; M.C. Michalski; B. Graulet; I. Verdier-Metz; C. Delbès (Journal of Dairy Science)
ABSTRACT: In semi-mountainous grass-based dairy systems, summer droughts frequently reduce grass availability, with implications for animal performance as well as milk and cheese quality. The objective of our study was to investigate the effect of a simulated summer forage shortage in a traditional semi-mountainous grass-based system versus a corn-based system with part-time grazing. During a 19-wk experiment, 26 Prim'Holstein and 14 Montbéliarde cows were blocked in 4 balanced groups of 10 cows. During the first 8 wk, 2 groups were fed a grass-based diet (75% of grazed grass, 25% of hay and concentrates) and the remainder were fed a corn-based diet (75% mixed ration, 25% of grazed grass). During the following 11 wk, one group in each feeding system was subjected to a reduction in grazed grass intake and a corresponding increase in indoor feeding, resulting in 50% of grazed grass for grass-fed cows and removal of grazed grass for corn-fed cows. Milk yield and composition were recorded during the whole trial, in addition to indoor individual intake. Grass intake was modeled to calculate feed efficiency and estimate methane emissions. At the end of the experiment, bulk milk from each group was sampled for physicochemical and microbiological analyses and processed into Cantal-type cheeses. After 9 wk of ripening, cheeses underwent physicochemical, microbiological and descriptive sensory analyses. Results showed that the complete removal of grazed grass in corn-based system had no effect on milk production but impaired feed efficiency; grass reduction in the grass-based diet better maintained milk yield, enhanced feed efficiency, and reduced methane emission intensity. Cheese softness increased with proportion of grass in the diet, and it was positively correlated with primary proteolysis (αS1-casein and β-casein breakdown) but negatively correlated with the C16:0/C18:1 ratio and the calculated fat melting point. Cheese from cows fed with more grazed grass were the yellowest and had the most pronounced flavors, as well as higher counts of heterofermentative lactobacilli and lactic acid bacteria. Removal of grazed grass from the corn-based diet led to cheese that was less yellow and had less flavor, in line with lower levels of secondary proteolysis. In conclusion, our study suggests that maintaining fresh herbage in corn-based diets is crucial for maintaining cheese quality without impairing animal performance. In grass-based systems, complementation with indoor feeding may have limited effects on product quality but promotes the maintenance of animal performance.